Data Distribusi pada Jumlah Kasus Penyakit Tuberculosis (TBC) Wilayah Kabupaten/Kota di Jawa Barat pada periode 2016 hingga 2021 - Jasmin, Nur Shabrina; Rianto, Rianto; Purwayoga, Vega (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2024)
Tuberculosis (TB) or Mycobacterium Tuberculosis is a germ that causes Tuberculosis infection that is contagious and attacks anyone. It is still a public health problem in Indonesia. The number of TB cases in West Java is high with a total of 101,272 TB cases that continue to increase by 21.12% each year. Therefore, it is necessary to analyze the normality test on the data of the number of TB cases in West Java to determine whether the data comes from a population that has a normal distribution or not. The method used in this research uses a qualitative method by observing 'OPEN DATA JABAR". The results of the normality test research by knowing the distribution of data using wrangling data and profiling data are known that the data is not normally distributed.